Improved Assessment of Chest pain Trial (IMPACT): assessing patients with possible acute coronary syndromes - Cullen, Louise; Greenslade, Jaimi H; Hawkins, Tracey; Hammett, Chris; O'Kane, Shanen; Ryan, Kimberley; Parker, Kate; Schluter, Jessica; Dalton, Emily; Brown, Anthony FT; Than, Martin; Peacock, W Frank; et al. (Medical journal of Australia, 2017)
Objective: To examine the safety and efficacy of the Improved Assessment of Chest pain Trial (IMPACT) protocol, a strategy for accelerated assessment of patients presenting to emergency departments (EDs) with chest pain. Design, setting and participants: IMPACT was an intervention trial at a single tertiary referral hospital (Royal Brisbane and Women's Hospital) during February 2011 – March 2014. 1366 prospectively recruited patients presenting to the ED with symptoms of suspected acute coronary syndrome (ACS) were stratified into groups at low, intermediate or high risk of an ACS. Intervention: High risk patients were treated according to NHFA/CSANZ guidelines. Low and intermediate risk patients underwent troponin testing (sensitive assay) 0 and 2 hours after presentation. Intermediate risk patients underwent objective testing after the second troponin test; low risk patients were discharged without further objective testing. Main outcome measures: The primary outcome was an ACS within 30 days of presentation. Secondary outcomes were ED and hospital lengths of stay (LOS). Results: The IMPACT protocol stratified 244 (17.9%) patients to low risk, 789 (57.7%) to intermediate risk, and 333 (24.4%) to high risk categories. The overall 30‐day ACS rate was 6.6%, but there were no ACS events in the low risk group, and 14 (1.8%) in the intermediate risk group. The median hospital LOS was 5.1 hours (IQR, 4.2–5.6 h) for low risk and 7.7 hours (IQR, 6.1–21 h) for intermediate risk patients. Conclusions: The IMPACT protocol safely and efficiently allowed a large proportion of patients presenting to EDs with chest pain to undergo accelerated assessment for risk of an ACS. Clinical trial registration: Australian New Zealand Clinical Trials Registry ACTRN12611000206921.